2021
DOI: 10.3389/fcell.2021.616520
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Ablation of the Catalytic AMPK α-Subunit SNF1 and Mitochondrial Matrix Protease CLPP Results in Pronounced Lifespan Extension

Abstract: Organismic aging is known to be controlled by genetic and environmental traits. Pathways involved in the control of cellular metabolism play a crucial role. Previously, we identified a role of PaCLPP, a mitochondrial matrix protease, in the control of the mitochondrial energy metabolism, aging, and lifespan of the fungal aging model Podospora anserina. Most surprisingly, we made the counterintuitive observation that the ablation of this component of the mitochondrial quality control network leads to lifespan e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…The observation of normal levels for valine, arginine/proline, glutamate/glutamine, and, in particular, ornithine in our ClpP-null MEFs suggests normal enzymatic activity remains for OAT even though it is accumulated and although the OAT hexamer might be misassembled. Additionally, a previous study of Podospora anserina ClpP deletion mutants also observed increased leucine/isoleucine, as opposed to decreased histidine levels [ 81 ]. The previously reported metabolome data in PRLTS3 patient 58955, where urinary excretion contained excess amounts of fumarate and oxo-glutarate [ 37 ], suggest that carbon flux in the TCA cycle occurs at high levels, possibly at the expense of specific amino acids as well as glucose.…”
Section: Discussionmentioning
confidence: 97%
“…The observation of normal levels for valine, arginine/proline, glutamate/glutamine, and, in particular, ornithine in our ClpP-null MEFs suggests normal enzymatic activity remains for OAT even though it is accumulated and although the OAT hexamer might be misassembled. Additionally, a previous study of Podospora anserina ClpP deletion mutants also observed increased leucine/isoleucine, as opposed to decreased histidine levels [ 81 ]. The previously reported metabolome data in PRLTS3 patient 58955, where urinary excretion contained excess amounts of fumarate and oxo-glutarate [ 37 ], suggest that carbon flux in the TCA cycle occurs at high levels, possibly at the expense of specific amino acids as well as glucose.…”
Section: Discussionmentioning
confidence: 97%
“…RNA isolation and cDNA synthesis was performed as previously described 53 . For each strain three biological replicates were analyzed three times each (technical replicates).…”
Section: Methodsmentioning
confidence: 99%
“…OAT may be misassembled but normal enzymatic activity remains. Also a previous study of Podospora anserina ClpP deletion mutants observed increased leucine/isoleucine, as opposed to decreased histidine levels [59]. The previously reported metabolome data in PRLTS3 patient 58955 where urinary excretion contained excess amounts of fumarate and oxo-glutarate [36] suggest that carbon flux in the TCA cycle occurs at high levels, possibly at the expense of specific amino acids as well as glucose.…”
Section: Tablementioning
confidence: 88%